Gender, Achievement, and Language Learning Strategies of Tertiary Students - Nina Ruzel T. Paggao; Rischelle G. Aggabao (RIRAI Publisher, 2022)
The paper aimed to determine the predominant strategies in language learning of tertiary students. It also examined the relationships between the students’ gender and their language learning strategies, the students’ achievement and the language learning strategies used according to their gender, and students’ achievement according to their gender. The researchers adopted a questionnaire which was floated to 300 first year students to gather data. The findings showed that students who were bisexuals often used metacognitive and cognitive strategies in learning English. Lesbians, on the other hand, frequently used social and compensation strategies to learn English while gays commonly employed social and meta-cognitive strategies. Male students regularly used social and memory strategies while female students often employed social and meta-cognitive strategies. It also appeared that there was significant relationship between language learning strategies used and students’ gender when it came to gay respondents only. Moreover, the study showed that language learning strategies used by the students did not influence their achievement in English. Lastly, findings revealed that the result of the mean grades of the students in their academic achievement was different from each gender. Therefore, students’ achievement in English varies according to gender.